Pengaruh Kompensasi dan Budaya Kaizen Terhadap Kinerja Karyawan Pt Bank Xxx Tbk Kantor Cabang Utama Cibubur, Depok - Rita Mardiana (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of Compensation and Kaizen Culture on employee performance partially and simultaneously. This research uses quantitative research with a correlational approach. The data collection techniques used questionnaires, observation and documentation. The study population was the staff and employees of PT. Bank XXX Tbk Main Branch Office Cibubur, Depok, totaling 54 people. The results showed that there was a strong relationship between compensation and kaizen culture together with employee performance so that it was empirically proven that there was a positive and significant effect of compensation and kaizen culture partially and simultaneously on the employee performance of PT. Bank XXX Tbk. Main Branch Office Cibubur, Depok.